Longitudinal Effects of Employees' Big Five Personality Traits on Internal Promotions Differentiated by Job Level in a Multinational Company - Tobias L. Kordsmeyer; Andrew B. Speer; Rafael Wilms; Rainer Kurz (Journal of Business and Psychology, 2024)
Abstract Promotions are central to individual career success. For organisations, it is crucial to identify and develop employees capable of higher-level responsibility. Previous research has shown that personality traits as inter-individual differences predict promotions. However, effects have mostly been examined on a broad factor level. This study investigated longitudinal effects of Big Five personality traits on both factor (neuroticism, extraversion, openness to experience, agreeableness, conscientiousness) and more detailed facet levels on promotions in employees of a multinational wholesale company ( N 0.167em=0.167em1774, n 0.167em=0.167em343 promoted). We also explored how personality differentially impacts promotional likelihood as a matter of target job level (individual contributor vs. first- or senior-level manager roles). Overall, associations with promotions were detected for neuroticism (negative) and conscientiousness (positive). At the more nuanced facet level, all Big Five factors had at least one personality facet that was significantly related to promotions. Additionally, personality-promotion relationships were generally stronger for lower- rather than higher-level promotions. Taken together, our findings demonstrate that employee personality traits have a meaningful impact on who will be promoted and should hence be considered in organisational personnel selection, personnel development, and performance management practices.
Keywords: 330; Big Five; Personality factors; Personality facets; Promotion; Job level